Understanding barriers to influenza vaccination among parents is important to improve vaccine uptake among children - Stephanie A. Davey; James Elander; Amelia Woodward; Michael G. Head; Daniel Gaffiero (Human Vaccines & Immunotherapeutics)
The COVID-19 pandemic has significantly altered public perceptions of vaccines, particularly among parents. In high-income countries like the United Kingdom (UK) and Australia, factors such as misinformation, the expedited approval process of COVID-19 vaccines and unique local challenges have contributed to vaccine hesitancy, resulting in uneven uptake across various vaccination programs. Despite efforts like school-based influenza vaccination programs in the UK and free influenza vaccines in Australia, vaccination rates continue to decline. This is especially concerning given the concurrent circulation of COVID-19 and influenza during the winter months, which places additional strain on healthcare systems. Drawing on existing evidence, this commentary examines key factors influencing childhood vaccination rates and provides preliminary policy recommendations to address these challenges. Three actionable recommendations are outlined, including strategies to counter misinformation, improve accessibility, and strengthen public trust in vaccination programs. These insights aim to guide the development of effective interventions to increase vaccination uptake.